2016
DOI: 10.1016/j.jsams.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of chronic ankle instability in a cohort of netball players

Abstract: Recurrent ankle sprain and perceived ankle instability are easily identifiable aspects of chronic ankle instability shown to be prevalent within this cohort. Additional research is required to quantify a cut-off value for mechanical instability. Club netball players were found to have more counts of moderate-severe perceived ankle instability and larger inversion-eversion angles when compared to the inter-district netball players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…In a recent systematic review of the prevalence of CAI in sporting populations, Attenborough et al 115 indicated that CAI is a highly prevalent condition (>25%) in sports such as handball, basketball, soccer and volleyball. This has been confirmed in recent investigations of collegiate and high school athletes in which the prevalence of CAI was ∼25% in those athletes with a previous history of injury 116 117. Within the performing arts population, such as ballet, more than 50% of the dancers with a history of ankle sprain report CAI 118.…”
Section: Section B: Mid-term and Long-term Consequences Of Lasssupporting
confidence: 52%
“…In a recent systematic review of the prevalence of CAI in sporting populations, Attenborough et al 115 indicated that CAI is a highly prevalent condition (>25%) in sports such as handball, basketball, soccer and volleyball. This has been confirmed in recent investigations of collegiate and high school athletes in which the prevalence of CAI was ∼25% in those athletes with a previous history of injury 116 117. Within the performing arts population, such as ballet, more than 50% of the dancers with a history of ankle sprain report CAI 118.…”
Section: Section B: Mid-term and Long-term Consequences Of Lasssupporting
confidence: 52%
“…Chronic ankle instability (CAI) is one of the most prevalent debilitating conditions in athletic populations [1,2]. A high percentage (23% to 61%) of athletes are identified as having CAI, with soccer, basketball, and volleyball being the most represented team sports [3,4,5,6]. In addition, recent research has highlighted that CAI is a public healthcare burden affecting not only athletic but also general populations [1].…”
Section: Introductionmentioning
confidence: 99%
“…Within the United States, the annual cost to treat one LAS is approximately $1,000 [18], with total direct and indirect costs for treatment of LAS exceeding $6 billion per year [20]. Additionally, 30 to 70 % of LAS patients develop a condition known as chronic ankle instability (CAI) [1,2,11,27,41]. Patients with CAI experience repetitive ankle sprains, feelings of instability following their initial LAS [24], are less physically active [30] and have a greater risk of developing post-traumatic ankle osteoarthritis [42] than individuals with no history of LAS.…”
Section: Introductionmentioning
confidence: 99%